2010
DOI: 10.1590/s1677-55382010000500002
|View full text |Cite
|
Sign up to set email alerts
|

Is male infertility a forerunner to cancer?

Abstract: Purpose: The frequency of testicular cancer and male infertility has been increasing in the past several decades. This article examines the relationship between male infertility and testicular cancer, concentrating particularly on causal links. Results: Both of these disorders are associated with testicular dysgenesis syndrome and have also been traced to mutations in genes involving DNA repair and tumor suppression, as well as environmental exposure. Conclusion:The identification and examination of these comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The higher risk of testicular cancer and poor semen quality over the past decades has drawn attention to the possibility that environmental xenoestrogens may be implicated. [37][38][39] Among xenoestrogens, phthalates are ubiquitous in human life. Hsu et al 40 and Han et al 41 reported that polycyclic aromatic hydrocarbons are associated with DNA damages.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 99%
“…The higher risk of testicular cancer and poor semen quality over the past decades has drawn attention to the possibility that environmental xenoestrogens may be implicated. [37][38][39] Among xenoestrogens, phthalates are ubiquitous in human life. Hsu et al 40 and Han et al 41 reported that polycyclic aromatic hydrocarbons are associated with DNA damages.…”
Section: Contribution Of Environmental Factorsmentioning
confidence: 99%
“…A full exploration of the potential underlying mechanisms is beyond the scope of this review, but there are some excellent reviews published in recent years. [50][51][52] The research is complicated by the fact that infertility itself is incompletely understood and is difficult to study. 53 It is generally accepted that disruptions of the testis germ cells and their regulation along with DNA repair failures are playing a large role in the association.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In fact, epidemiological studies in males who presented fertility problems tend to lean toward an enhanced risk of testicular germ cell tumor (30). The development of TC is associated with many chromosomal abnormalities and this raises the problem for close monitoring of these patients.…”
Section: Germ Cell Development Infertility and Testicular Cancer Inmentioning
confidence: 99%